Orthorexia Nervosa: Disorder or Not? Opinions of Dutch Health Professionals - Ryman, Frida V. M.; Cesuroglu, Tomris; Bood, Zarah M.; Syurina, Elena V (Frontiers in Psychology, 2019)
Introduction: Orthorexia nervosa (ON) is a condition that is characterized by a pathological obsession with eating foods one considers healthy and has been recently suggested as a new possible diagnosis. However, there is limited published research on health professionals’ recognition, ideas and opinions regarding the diagnosis and classification of Orthorexia Nervosa. Purpose: The aim of this mixed-methods study was to gain insight into the perspectives of clinically active health professionals on ON, and into their opinions on if and how the disorder should be classified. Results: Psychologists, psychiatrists, dietitians and physiotherapists in the Netherlands (n=160) participated by responding to a self-administered questionnaire. Most health professionals (78%) reported that they thought that ON should have its own diagnosis. This opinion was more common in physical health professionals than in mental health professionals. A majority (74%) agreed that ON fits within the Diagnostic and Statistical Manual of Mental Disorders (DSM) category Eating and Feeding Disorders. Interviews with 15 mental health professionals were analyzed using code frequencies and continuous comparisons. Mental health professionals reported believing that ON is prevalent in the general population and that a separate diagnosis would have both advantages and disadvantages for health professionals and patients. Interview participants described the typical ON patient as being young, female, and highly educated; characteristics that overlap with typical anorexia nervosa and obsessive compulsive disorder cases. Conclusion: The results suggest that some health professionals from a heterogenous sample in the Netherlands think ON should have a separate diagnosis in the DSM, however, the study needs to be replicated to allow for further generalization. Methodological design of this study may be utilized in future research with similar aims. The findings can serve as a foundation for investigation of individuals’ experiences of distress caused by ON, and further refinement of the diagnostic criteria.